Electro-thermal modelling of redox flow-batteries with electrolyte swapping for an electric ferry. (October 2022) - Woodfield, Richard; Glover, Stephen; Watson, Robert; Nockemann, Peter; Stocker, Richard
Abstract: Vanadium redox flow-batteries in coastal ferry applications have the potential to help bring down the carbon footprint of the shipping industry. There is a lack of research focused on vanadium redox flow-batteries in transport applications due to their low energy density, though electrolyte swapping offers benefits whereby the depleted electrolyte can be rapidly exchanged for a fully charged supply. Vanadium redox flow-batteries also benefit from significantly higher cycle life when compared to Li-ion and fuel cell technologies, offering potential for lower cost per year of ownership. A vanadium redox flow-battery coastal ferry is electro-thermally modelled to identify whether it is feasible in terms of energy capacity, temperature limits, carbon footprint and cost. The ferry journeys between two ports, where each port is equipped with a flow-battery to provide electrolyte swapping. An Equivalent Circuit Model is utilized to model the battery response, while the thermal model predicts the electrolyte temperature based on the conservation of energy. Shunt current and pumping losses are considered in the model. It was found that vanadium redox flow-batteries show real potential for the decarbonisation of the shipping industry. Battery temperature is kept within the safe operating limits, while offering a cost per voyage close to that of a diesel system, with significant reductions in CO2 output. Highlights: An electro-thermal redox flow battery ferry model incorporating shunt currents and pumping losses is developed and compared to a diesel system Vanadium redox flow batteries (VRFB) are shown to be viable candidates for E -ferries Swapping electrolyte using pre-chambers offers improved ferry efficiency and increased range It is shown that cooling is only required in the batteries located at the ports The VRFB ferry is able to compete with the operational costs of a diesel system while showing a threefold reduction in CO2